Notes on your sudden disappearance : a novel - Espach, Alison, 1984- (Henry Holt and Company, 2022)
"The summer before Sally Holt starts the eighth grade begins as a gloriously uneventful one, full of family trips to the beach and long afternoons at the local pool with her older sister Kathy, which they mostly use as an excuse to ogle Billy Barnes, who works the concession stand there. Their fascination with him is one of the few things the increasingly different sisters have in common. By summer's end Billy and Kathy are an item-an unthinkable stroke of luck that ends in an even more unthinkable tragedy. Set over the course of fifteen years, charting shared history and missed connections, Notes on your sudden disappearance is both a breathtaking love story between two broken people who are unexplainably, inconveniently drawn to each other, and a wry, sharply observant coming-of-age story that looks at the ways the people we love the most continue to shape our lives long after they're gone"--